Salivary testosterone levels and pain perception exhibit sex-specific association in healthy adults but not in patients with migraine - Pan, Li-Ling Hope; Chen, Shih-Pin; Ling, Yu-Hsiang; Wang, Yen-Feng; Lai, Kuan-Lin; Liu, Hung-Yu; Chen, Wei-Ta; Huang, William J.; Coppola, Gianluca; Treede, Rolf-Detlef; Wang, Shuu-Jiun (The journal of pain, 2024)
This study investigated the sex-specific associations between pain perception and testosterone levels in healthy controls (HCs) and patients with migraine. Male and female HCs and migraine patients were recruited. A series of questionnaires were completed by the participants to evaluate their psychosocial profiles, which included data on mood, stress, and sleep quality. Heat pain thresholds and suprathreshold pain ratings at 45 °C (referred to as the pain perception score [PPS]) were assessed using the Thermode system. Salivary testosterone levels were analyzed using a commercial enzyme-linked immunosorbent assay kit. A total of 88 HCs (men/women: 41/47, age: 29.9 ± 7.7 years) and 75 migraine patients (men/women: 30/45, age: 31.1 ± 7.7 years) completed all assessments. No significant differences were observed in either the psychosocial profiles or heat pain thresholds and PPSs between the sexes in the control and migraine groups. A positive correlation between testosterone levels and PPSs was identified in the male controls (r = .341, P = .029), whereas a negative correlation was identified in the female controls (r = −.407, P = .005). No such correlations were identified in the migraine group. This study confirms that a negative association is present between PPSs and testosterone levels in female controls, which is in line with the findings that testosterone is associated with reduced pain perception. Our study is the first to demonstrate a sex-specific association between PPSs and testosterone levels in HCs. Moreover, this study also revealed that the presence of migraine appears to disrupt this association. - Perspective - This study revealed that testosterone levels demonstrate opposite associations with pain perception in healthy men and women. However, the presence of migraine appears to disrupt this sex-specific association.